SYNTHESIS OF ZINC-DIFATTYALKYLDITHIOCARBAMATES AND THEIR ANTIOXIDANT ACTIVITIES - Komar Sutriah; Zainal Alim Mas’ud; Tun Tedja Irawadi (Universitas Gadjah Mada, 2012)
Zinc-difattyalkyldithiocarbamates are organosulfur compounds with many functions, including as an antioxidant in a lubrication system. They were synthesized by reacting secondary fatty amine with ZnCl2 and CS2 giving result zinc-difattyalkyldithiocarbamates of around 77-87%. The synthesized products were characterized using infrared (IR) spectroscopic techniques. The IR spectra of zinc-difattyalkyldithiocarbamates showed sharp bands at 1450-1550 cm-1 for thioureida v (C-N), 950-1050 cm-1 for v (C-S), and in the far-red area 300-400 cm-1 for sulfur-metal bond. Products recovery was evaluated by AAS and the purity was analyzed by HPLC. Seven variants of zinc-difattyalkyldithiocarbamates were obtained. Antioxidant activity was evaluated by rancimat test regarding their induction time. At 125 ppm levels all variants showed higher value in each of their induction time as compared to those of butylated hydroxyanisole and butylated hydroxytoluene, commercial antioxidants No.1, and commercial antioxidants no.2. Three variants, i.e. Zn-bis(dilauryl)dithiocarbamate, Zn-bis(laurylpalmityl)dithiocarbamate, and Zn-bis(laurylstearyl)dithiocarbamate had higher values in their induction time than the other variants. The values are 16.67, 26.54, and 16.11 h, respectively.